Respuesta :

[tex]f(x)=x^4-ax^3+bx+c[/tex]

By the polynomial remainder theorem, dividing [tex]f(x)[/tex] by [tex]x-2[/tex] three times leaves a remainder of 0; we have

[tex]\dfrac{x^4-ax^3+bx+c}{x-2}=x^3+2x^2+(4-a)x+8+b-2a+\dfrac{16+c+2b-4a}{x-2}[/tex]

[tex]\implies16+c+2b-4a=0[/tex]

Dividing the quotient by [tex]x-2[/tex] again leaves a remainder of 0:

[tex]\dfrac{x^4-ax^3+bx+c}{(x-2)^2}=x^2+4x+12-a+\dfrac{32+b-4a}{(x-2)^2}[/tex]

[tex]\implies32+b-4a=0[/tex]

and again:

[tex]\dfrac{x^4-ax^3+bx+c}{(x-2)^3}=x+6+\dfrac{24-a}{(x-2)^3}[/tex]

[tex]\implies24-a=0[/tex]

Then

[tex]24-6a=0\implies a=24[/tex]

[tex]32+b-4a=0\implies b=64[/tex]

[tex]16+c+2b-4a=0\implies c=-48[/tex]

ACCESS MORE